2016
DOI: 10.1111/dar.12434
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of research show alcohol to be a cause of intimate partner violence: Future research needs to identify who to treat and how to treat them

Abstract: COMMENTARYThirty years of research show alcohol to be a cause of intimate partner violence: Future research needs to identify who to treat and how to treat them ABSTRACT Research over the past 30 years has demonstrated that excessive alcohol use meets all of the epidemiological criteria for causality. While neither a necessary nor a sufficient cause, excessive alcohol use does contribute to the occurrence of partner violence and that contribution is approximately equal to other contributing causes such as gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
147
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 26 publications
9
147
1
3
Order By: Relevance
“…Leonard and Quigley highlight the importance of treating those who drink excessively and perpetrate IPV, an area where interventions have shown some impact . Our theoretical framework expands consideration of research and interventions to address the following: societal and cultural norms and expectations, the potential role of guardians and handlers, the impact of drinking generally on the relationship and perceptions of the role of victims' drinking—areas that have received little attention to date.…”
Section: Alcohol's Role In Ipv—the Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…Leonard and Quigley highlight the importance of treating those who drink excessively and perpetrate IPV, an area where interventions have shown some impact . Our theoretical framework expands consideration of research and interventions to address the following: societal and cultural norms and expectations, the potential role of guardians and handlers, the impact of drinking generally on the relationship and perceptions of the role of victims' drinking—areas that have received little attention to date.…”
Section: Alcohol's Role In Ipv—the Way Forwardmentioning
confidence: 99%
“…
We commend Leonard and Quigley [1] for their strong summary of the evidence of the impact of alcohol on intimate partner violence (IPV). Rather than reiterating crucial points that they have made about the importance of addressing alcohol use among men for whom such use is linked to IPV, we extend their discussion to implications for the broader context for preventing alcohol-related IPV (AIPV).Leonard and Quigley focus on identifying men for whom the pharmacological effects of alcohol reduce inhibitory cues sufficiently for them to engage in IPV.
…”
mentioning
confidence: 99%
“…Alcohol use is a prevalent and well-established risk factor for IPV; however, evidence primarily comes from HICs (Foran & O'Leary, 2008;Abbey et al 2014;Leonard & Quigley, 2017). Three theories were originally posited to explain the relationship between alcohol use and IPV (Foran & O'Leary, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence such as that from a case cross‐over study of violent offenders which showed that drinking alcohol in the preceding 24 h made commission of a violent offence 13 times more likely than during periods of non‐exposure to alcohol indicates that the alcohol and violence association is more than just coincidental. The association between alcohol use and violence applies also to IPV, as succinctly argued and evidenced in this issue by Leonard and Quigley . They conclude that alcohol contributes to both the occurrence and severity of IPV.…”
mentioning
confidence: 77%